Post hoc test of Indonesia domestic systemically important banks performance at the ASEAN-5 level - Fongnawati Budhijono; Sugiarto Sugiarto; Muhammad Fuad (President University, 2021)
This study aims to examine whether the existence of strong banking interconnectivity in ASEAN brings about equality in bank performance, especially for banks that are classified as Domestic Systemically Important Banks (D-SIB). This study traces the performance of D-SIB banks operating in Indonesia at the ASEAN-5 level (Indonesia, Malaysia, Thailand, the Philippines, and Singapore) in 2007-2019. ROA is used to indicate bank performance, especially related to bank profitability, which is an important aspect for bank sustainability. The research data was obtained from the official websites of financial organizations and institutions such as World bank, IMF, OJK, Bloomberg terminal, and financial statements of banks in ASEAN-5 with a sample of 31 D-SIB banks. By using descriptive analysis and ANOVA as well as post hoc tests and scatter diagrams, the results of the study show that D-SIB banks operating in Indonesia have an ROA performance that dominates D-SIB banks which are classified as top 10 average ROA. It can be seen that D-SIB banks operating in Indonesia are not inferior to DSIB banks operating overseas and even proven to be able to outperform D-SIB banks operating overseas.